Citra Kota Batam Sebagai Kota Pariwisata Menurut Wisatawan Yang Berkunjung Ke Kota Batam - D Sianturi, Grace Honey; Purwanti, Angel (SCIENTIA JOURNAL, 2021)
Tourism is not new, currently tourism is an industrial product that is increasingly in demand to be visited. Local governments are responsible for developing and managing all the potentials of their respective regions to be able to attract foreign and local tourists. As a tourism destination, Batam City has a geographic area in one or more administrative areas that have accessibility, tourism facilities, public facilities, tourist attractions to complement the realization of tourism. The research is carried out on the basis of samples, the analysis can use descriptive statistics, descriptive statistics themselves can be used if the research only needs to present sample data and does not want to draw conclusions for the population where the sample is obtained, and testing in this study uses descriptive testing using several tests through assistance software SPSS 23. This type of research is quantitative research that will study that will test the image of the city which consists of cognitive images, unique images and affective images. Sampling using simple random sampling technique. Keywords: Tourism, City Image